Innovative Leadership and Its Role in Building the Learning Organization An Exploratory Study Of The Opinions Of A Sample Of Managers Of Public Sector Banks In Erbil City - Ahlam Ibrahim ali; Muhsin Othman Hassan (QALAAI ZANIST JOURNAL, 2020)
The purpose of this research is to understand the role of Innovative Leadership in building the educated organization in the public sector banks. Thus by identifying the relationship and the impact of each of the (Efficiency and take responsibility, Confidence in self and followers, Creativity) as the dimensions president to Creative Leadership as well as the (Strategic Leadership, Group Learing, Participation Vision) as the dimensions of educated organization. Several questions of intellectual and practical were used to discuss the research problem of knowing the dimensions of Creative Leadership and their relationship and impacts on the learning organization in public sector banks. In order to carry out the primary research a sample of (85) managers of the public banking sector from the totals of the (196) managers in the city of Erbil were choosing. The main method of the research was a descriptive approach and analytical approach. A questionnaire form was designed as the main tool for data collection, a range of appropriate statistical methods were used to verify the assumptions of research and to address the research problem. The research highlighted several outcomes; the most important was that there is a significant degree of relationship between the dimensions of Creative Leadership and building the educated organization. The research also made several recommendations related to the practical aspects and the need to maintain the Creative Leadership because of their significant role in building the learning organization like the banks surveyed.